Application of topological optimization technique to running shoe designing - Nishiwaki, T.; Nonogawa, M. (Procedia Engineering, 2015)
This paper describes the application of topological optimization method to heel counter in the practical designing process of running shoes. The heel counter has an important role to control the excessive calcaneous eversion in a series of running motion. This control is called as shoe stability, which is one of the most important requirement functions in shoe designing. At the same time shoe weight should be reduced because the runners` fatigue can be intimately interrelated with shoe weight. Both these functions, stability and lightness are conflicting parameters. The optimization method has been developed to satisfy some requirement functions and widely applied to industrial fields. By using the topological optimization method, the optimized heel counter with enough stability and weight reduction was practically designed. In order to check the validity of the counter manufactured, the stability of running shoes with the heel counter was quantitatively evaluated in the practical running motion analyses and compared with that of the conventional heel counter. Therefore it was confirmed that the topological optimization method was so powerful tool in the practical designing process of running shoes.